Gerakan Sosial Berbasis Gender di Media Sosial: Tinjauan Sosiologis terhadap Kampanye #MeToo dan #NikahMuda - Chaniago, Hayatun Nufus (Yayasan Albahriah Jamiah Indonesia, 2025)
Social media has become a new arena for the articulation of identity, struggle, and social change, including on gender issues. The #MeToo and #NikahMuda campaigns represent two gender-based social movements operating digitally, but with opposing orientations and narratives: one is emancipatory and critical of sexual violence, while the other tends to be conservative and promotes local religious or cultural values ​​about early marriage. This study aims to analyze the dynamics of these two campaigns sociologically by exploring the construction of gender meanings constructed through social media and uncovering the terrain of contestation between modern and traditional values. The study uses a descriptive qualitative method with data collection techniques through social media observation, documentation of campaign posts, and literature studies. The analysis is conducted using the approach of new social movement theory and the social construction of gender. The results show that #MeToo functions as a medium of resistance against patriarchal structures and opens up space for victim narratives, while #NikahMuda emphasizes the idealization of women's roles in the domestic sphere and social reproduction. Both campaigns use visual strategies, emotional narratives, and religious/cultural symbolism to build legitimacy. However, #MeToo tends to disrupt dominant norms, while #NikahMuda seeks to affirm existing norms. In conclusion, social media has become a terrain for contesting the meaning of gender between emancipatory and conservative discourses, reflecting the complexity of power relations, identity, and values in contemporary digital society.